2021
DOI: 10.3390/app11136051
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Underwater Wireless Optical Communication Channel Based on a Comprehensive Multiparameter Model

Abstract: A comprehensive multiparameter model is proposed for underwater wireless optical communication (UWOC) channels to integrate the effects of absorption, scattering, and dynamic turbulence. The simulation accuracy is further improved by the combined use of the subharmonic method and the strict sampling constraint method by comparing the phase structure function with the theoretical value. The average light intensity and scintillation index are analyzed using the channel parameters of absorption, scattering, turbu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 30 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…AND WATER TYPES The most widely used theoretical basis to model the effects of attenuation is the Beer-Lambert's law [15]. In UWOC, the received power through the water medium can be obtained via the law as expressed in (1) [1].…”
Section: Beer Lambert's Law Attenuation Coefficientmentioning
confidence: 99%
See 1 more Smart Citation
“…AND WATER TYPES The most widely used theoretical basis to model the effects of attenuation is the Beer-Lambert's law [15]. In UWOC, the received power through the water medium can be obtained via the law as expressed in (1) [1].…”
Section: Beer Lambert's Law Attenuation Coefficientmentioning
confidence: 99%
“…The data rate and the transmission distance are reduced in the presence of salt. Cai et al [15] proposed a multiparameter model to integrate the effects of absorption, scattering and turbulence in underwater optical communication systems using Beer Lambert's law and Monte Carlo. An increase in transmission distance worsens the attenuation and significantly increases the fluctuation of light signals.…”
Section: Introductionmentioning
confidence: 99%
“…A performance evaluation and analysis has been illustrated in [37], where in order to examine the effects of turbulence and further-induced fading in UWOC channels, the fading effect has been treated as a multiplicative coefficient together with the coefficients of scattering and absorption. In their work of Cai, R. et al [38], the authors have developed a detailed multiparameter model for the UWOC channel. The findings showed that by boosting the transmitting light power, bit error rate (BER) performance may be significantly improved under weak or medium turbulence.…”
Section: Design Challengesmentioning
confidence: 99%
“…The PDF models fitted based on WOS statistics are forcefully supported by the hydrodynamics and wave optics theories, making their accuracy and validity guaranteed. Relevant researches have been reported over the years [22]- [24]. Zhang et al and Shishter et al selected the Log-normal distribution [22] and Gamma distribution [23] to fit the simulation data, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al and Shishter et al selected the Log-normal distribution [22] and Gamma distribution [23] to fit the simulation data, respectively. Gao et al applied the Weibull distribution to model the fading effect under various turbulent situations [24]. While progress has been made in PDF modeling based on WOS, the simulation scenarios are still confined to atmospheric turbulence, other than that, the simulation process and the details of parameter design are not provided.…”
Section: Introductionmentioning
confidence: 99%